Efektifitas Perda Kabupaten Klungkung No 2 Tahun 2010 dalam Upaya Pelestarian Lingkungan di Pantai Watu Klotok - Ketut Danu Yudistira; Luh Putu Suryani; Anak Agung Sagung Laksmi Dewi (Jurnal Konstruksi Hukum, 2022)
The environmental condition in Klungkung Regency has shown some signs of increasing environmental damage and pollution. In the context of environmental protection, the Klungkung Regency Government issued Regional Regulation Number 2 of 2010 concerning Control of Environmental Damage and Pollution. Based on the description, the problems faced are how effective Perda No. 2 of 2010 is and what are the obstacles in enforcing Perda No. 2 of 2010. The type of research used is empirical legal research with data collection techniques and field interviews. The effectiveness of the Regional Regulation in an effort to stop the level of pollution on the Watu Klotok beach with preventive and repressive efforts through: administrative sanctions in the form of verbal warnings, written warnings, fines or civil sanctions for environmental damage or pollution. The obstacles encountered include: factors from the implementation of the law itself, factors from law enforcement officials, community culture, economy and public awareness. The conclusion of the research shows that the effectiveness of the regulation has not been implemented effectively by law enforcers in terms of imposing sanctions. Therefore, the Klungkung Regency Government must be more firm and wise in implementing the existing legal regulations.